Plasma Markers of Neurodegeneration Are Raised in Friedreich’s Ataxia - Zeitlberger, Anna M.; Thomas-Black, Gilbert; Garcia-Moreno, Hector; Foiani, Martha; Heslegrave, Amanda J.; Zetterberg, Henrik; Giunti, Paola (Frontiers in Cellular Neuroscience, 2018)
Background: Friedreich’s ataxia (FRDA) is the most common autosomal recessive ataxia. Disease-modifying treatments are not available yet; however, several compounds are currently under investigation. As a result, there is a growing need for the identification of robust and easily accessible biomarkers for the monitoring of disease activity and therapeutic efficacy. The simultaneous measurement of multiple brain-derived proteins could represent a time- and cost-efficient approach for biomarker investigation in pathologically complex neurodegenerative diseases like FRDA. Objectives: To investigate the role of plasma neurofilament-light chain (NfL), glial fibrillary acidic protein (GFAP), total tau (t-tau) and ubiquitin C-terminal hydrolase L1(UCHL1) as biomarkers in FRDA. Additionally, NfL measurements derived from the novel multiplex assay were compared to those from an established NfL singleplex assay. Methods: In this study, an ultrasensitive Single molecule array (Simoa) 4-plex assay was used for the measurement of plasma NfL, GFAP, t-tau and UCHL1 in 33 FRDA patients and 13 age-matched controls. Differences in biomarker concentrations between these groups were computed and associations with genetic and disease related parameters investigated. Additionally, the agreement between NfL measurements derived from the 4-Plex and an established Simoa NfL singleplex assay was assessed. Results: Mean plasma NfL, GFAP and UCHL1 levels were significantly higher in FRDA patients than in controls (NfL: p<0.001; GFAP: p=0.006, and UCHL1: p=0.020). Conversely, there was no significant difference in concentrations of t-tau in the patient and control group (p=0.236). None of the proteins correlated with the GAA repeat length or the employed measures of disease severity. The individual NfL values derived from the two assays showed a strong concordance (rc=0.93). Although the mean difference of 1.29 pg/mL differed significantly from 0 (p=0.006), regression analysis did not indicate the presence of a proportional bias. Conclusion: This is the first study demonstrating that NfL, GFAP and UCHL1 levels are raised in FRDA, potentially reflecting ongoing neuronal degeneration and glial activation. Further studies are required to determine their role as marker for disease activity and progression. Furthermore, the novel 4-plex assay appears to be a valid tool to simultaneously measure brain-derived proteins at extremely low concentrations in the peripheral circulation.